Evidence for and against a pathogenic role for reduced γ-secretase activity in familial Alzheimer’s disease - Verdile, Giuseppe; Jayne, T.; Newman, M.; Sutherland, G.; Munch, G.; Musgrave, I.; Moussavi Nik, H.; Lardelli, M. (IOS Press, 2016)
The majority of mutations causing familial Alzheimer’s disease (fAD) have been found in the gene PRESENILIN1 (PSEN1 ) with additional mutations in the related gene PRESENILIN2 (PSEN2 ). The best characterized function of PRESENILIN (PSEN) proteins is in γ-secretase enzyme activity. One substrate of γ-secretase is encoded by the gene AMYLOID BETA A4 PRECURSOR PROTEIN (A βPP/APP) that is a fAD mutation locus. AβPP is the source of the amyloid-β (Aβ) peptide enriched in the brains of people with fAD or the more common, late onset, sporadic form of AD, sAD. These observations have resulted in a focus on γ-secretase activity and Aβ as we attempt to understand the molecular basis of AD pathology. In this paper we briefly review some of the history of research on γ-secretase in AD. We then discuss the main ideas regarding the role of γ-secretase and the PSEN genes in this disease. We examine the significance of the “fAD mutation reading frame preservation rule” that applies to PSEN1 and PSEN2 (and A βPP ) and look at alternative roles for AβPP and Aβ in fAD. We present a case for an alternative interpretation of published data on the role of γ-secretase activity and fAD-associated mutations in AD pathology. Evidence supports a “PSEN holoprotein multimer hypothesis” where PSEN fAD mutations generate mutant PSEN holoproteins that multimerize with wild type holoprotein and dominantly interfere with an AD-critical function(s) such as autophagy or secretion of Aβ. Holoprotein multimerization may be required for the endoproteolysis that activates PSENs’ γ-secretase activity.